2006
DOI: 10.1111/j.1365-2567.2006.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

A T2 cytokine environment may not limit T1 responses in human immunodeficiency virus patients with a favourable response to antiretroviral therapy

Abstract: Summary Low‐level production of interferon‐γ (IFN‐γ) marks human immunodeficiency virus (HIV)‐induced immunodeficiency and has been ascribed to a bias towards T2 cytokines. This was investigated in two cross‐sectional studies of HIV patients who were immunodeficient when they began antiretroviral therapy (ART) and had stable increases in CD4 T‐cell counts. Blood leucocytes were assessed unstimulated or after stimulation with cytomegalovirus (CMV), anti‐CD3 or mitogen. IFN‐γ and interleukin (IL)‐5 responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Our findings of levels of PHA-induced, PBMC-derived IL-4 and IL-5 production in HIV-infected subjects that are significantly higher than those in healthy adult controls (with or without PD-1/PD-L1 blockade; Fig. 6) support previous observations of elevated Ig E levels and eosinophilia in HIV-infected subjects (2,11,12). A comparison of mitogen-and antigen-induced lymphoproliferative responses and TH-1/TH-2 cytokine production in the presence and absence of coinhibitory signaling blockade may lead to an improved functional immune measure for monitoring HIV disease progression or response to antiviral therapy and is the subject of further study.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings of levels of PHA-induced, PBMC-derived IL-4 and IL-5 production in HIV-infected subjects that are significantly higher than those in healthy adult controls (with or without PD-1/PD-L1 blockade; Fig. 6) support previous observations of elevated Ig E levels and eosinophilia in HIV-infected subjects (2,11,12). A comparison of mitogen-and antigen-induced lymphoproliferative responses and TH-1/TH-2 cytokine production in the presence and absence of coinhibitory signaling blockade may lead to an improved functional immune measure for monitoring HIV disease progression or response to antiviral therapy and is the subject of further study.…”
Section: Discussionsupporting
confidence: 81%
“…The inverse relationship between immunoglobulin levels and IFN-g responses in HIV-infected patients on ART cannot simply be explained by a bias towards type (T) 2 cytokine production, because we have shown that IgE levels correlated inversely with mitogen-induced production of both IL-5 (T2) and IFN-g (T1) mRNA [39]. Weak positive correlations were also evident between levels of IFN-g, IL-4d2 (both T1), IL-4 and IL-5 (both T2) mRNA after mitogenic stimulation.…”
Section: Discussionmentioning
confidence: 77%
“…We subsequently associated CMV/encephalitis IRD with high and rising levels of plasma IL-6 and sCD30 (133,134). At the time, this was associated with a Th2 cytokine environment, but subsequent data shed doubt on this interpretation of elevated sCD30 (111).…”
Section: Ird Manifested As CMV Retinitis or Viral Encephalomyelitis: mentioning
confidence: 96%